The Causal Relationship Between Money Supply , Inflation and Exchange Rate in Iraq for the Period ( 1990-2011) - محمود, محمود محمد; عاشور, احسان جبر (Journal of Economics and Administrative Sciences, 2014)
The paper aims to measure the impact of monetary policy on price stability , by testing the causal relationship between the money supply,  inflation rate and the exchange rate , In order to prove that the  inflation is a monetary phenomenon in the Iraqi economy , and that the exchange rate is controlled in the money supply , the money supply as an endogenous  variable continued we found by using the standard tests to the existence of a single co-integration  between the money supply and the rate of inflation and the money supply and the parallel exchange rate, This confirms the existence of a long-term relationship between the variables , It also confirmed the results of the vector error correction model (VECM) for the existence of a long-term causal relationship, one-way from the money supply to inflation. This confirms that inflation in the Iraqi economy a monetary phenomenon and that the expansion in the money supply may hurt economic stability . And also the existence of a causal relationship long-term, the direction of one of the parallel exchange rate to the money supply, Which refers to the exchange rate effect on economic stability . And demonstrates the use of the exchange rate channel, mainly by monetary policy to transfer the monetary effect economic activity